A systematic review on wound healing - MD, Aftab Quraishi; J, Bhuvaneshwari; C, Roopa (International Journal of Indigenous Herbs and Drugs, 2023)
The body’s initial line of defence, the skin protects the inside organs from heat, chemical, and mechanical harm. It has a highly developed immune system that protects the body from harmful illnesses. The body’s natural response to tissue damage is wound healing. But wound healing is a complicated process that involves a wide range of cell types, cytokines, mediators, and the vascular system interacting with one another. It is a complex, strictly controlled process that is essential to retaining all other skin functions in addition to the skin’s barrier function. Numerous factors, both modifiable and non-modifiable, can impact this process. In order to successfully restore the damaged tissue, wound healing is a dynamic process supported by a variety of cellular processes, including as homeostasis, inflammation, proliferation, and remodelling. These activities must be properly integrated with one another. When there is damage to the skin, bacteria can swiftly infiltrate the tissues behind the skin, leading to life-threatening infections and chronic wounds. Natural phytomedicines with significant pharmacological qualities have been used extensively and successfully to treat wounds and prevent infections. Phytotherapy has been used for millennia to effectively cure skin wounds and delay the formation of infections. This study focuses on cutaneous wound healing and highlights the classical wound healing phases because wound healing occurs in many regions of the human body. Changes in any one of these stages may encourage the development of chronic wounds and hinder their healing. Numerous plants have been shown to aid in wound healing through a variety of processes.